Estudo das interações polifenol-proteína e das reações de escurecimento não-enzimático para o processamento de cajuína - Damasceno, Leandro Fernandes (2007)
The cashew, a fruit from Brazilian Northeast is used to produce juice due to its flavor and vitamin C richness. However, its acceptance is limited due to its astringency. Cajuína is a derivate product appreciated by its characteristic flavor, freshness and lack of astringency, due to tannin removal. Cajuína is a light yellow beverage made from clarified cashew juice and sterilized after bottling. It differs from the integral and concentrated juice by the clarification and thermal treatment steps. Many problems such as haze and excessive browning could appear if these steps are not controlled. The objective of this work was divided into two stages with the aim to supply process information in order to obtain a good quality product with uniform characteristics (sensory and nutritional). Polyphenol-protein interaction was studied at the clarification step, which is an empirical process, to provide values on the amount of clarifying solution (gelatin) that must be added to achieve a complete juice clarification. Clarification essays were performed with juice dilutions of 1:2 and 1:10 and the effect of metabissulfite and tannic acid addition was evaluated. It was not possible to establish a clarification point. Metabissulfite did not influenced the clarification process however tannic acid addition displaced the clarification point, showing the difficulty visual monitoring of the process. Thermal treatment of clarified juice was studied at 88, 100, 111 e 121 °C. To evaluate the non-enzymatic browning, vitamin C, 5-hidroximetilfurfural (5-HMF) and sugar variation were correlated with color parameters (reflectance spectra, color difference and CIELAB). Kinetic models were obtained for reflectance spectra, ascorbic acid and 5-HMF. It was observed that 5-HMF introduction followed a first order kinetic rate at the beginning of the thermal treatment and a zero order kinetic at later process stages. An inverse correlation was observed between absorbance at 420 nm and ascorbic acid degradation, which indicates that ascorbic acid might be the principal factor on cajuína non-enzymatic browning. Constant sugar concentration showed that this parameter did not contribute directly to the nonenzymatic browning. Optimization techniques showed showed that to obtain a high vitamin C and a low 5-HMF content, the process must be done at 120 ºC. With the water-bath thermal treatment, the 90 °C temperature promoted a lower ascorbic acid degradation at the expense of a higher 5-HMF level